More from less : the surprising story of how we learned to prosper using fewer resources- and what happens next - McAfee, Andrew (London : Simon & Schuster, 2019)
A surprising analysis of the decline in consumption of natural resources despite the explosion of goods, prosperity, and population.
Includes index.
Keywords: Consumption (Economics) -- Environmental aspects; Natural resources -- Environmental aspects; Conservation of natural resources